Location and geographic diversification patterns of Spanish financial institutions: Implications for growth, 1989-2009 - Luisa Alamá; Emili Tortosa-Ausina (European Regional Science Association (ERSA), 2010)
Over the last twenty years, the Spanish banking industry has been deeply reshaped in several respects. One of the features that has allowed for it has been the geographic expansion of most savings banks, which could not enter other markets different from their natural market before 1989. Since then, they have been expanding geographically into other regions (different from their regions of origin) at a remarkable pace. Almost simultaneously, except for the hiatus of the 1993 crisis, the Spanish economy has grown at remarkable annual rates, a growth pattern which has stopped suddenly in 2008. Under these circumstances, this paper has several goals. The first one consists of exploring which the geographic diversification patterns of Spanish financial institutions have been during 1989-2009. This goal extends previous analyses in two main ways: (i) we include not only commercial and savings banks but also credit unions, which are very important in rural communities affected by financial exclusion; (ii) we evaluate location patterns from a spatial statistics perspective, whose importance in regional science has been demonstrated, but have not been considered for analyzing financial institutions' location patterns. Once these patterns are determined, the second main goal of the paper consists of analyzing the links between these patterns' and firms' performance, in terms of efficiency and productivity. Finally, there is a large body of literature analyzing the links between financial development and growth from a country or even regional perspective. In this article, the database we use enables the possibility of extending this goal to the municipal case. This is important, since there are some Spanish provinces such as Madrid with population above 6 million whose comparison with other much smaller provinces (whose population is well below 100,000 inhabitants) is rather uninformative. Results indicate: (i) the location and diversification patterns vary mostly across firms and by type of firm; (ii) it is difficult to establish a linear relationship between banks' performance and geographic diversification; (iii) the evaluation of growth and financial development at municipal level indicates that some communities have experienced financial exclusion.
Keywords: 330; bank; branches; municipality